The Effect of Work Stress, Work Motivation, Organizational Culture On Work Performance: Leadership Style As Moderation - Purnama, Yessa Satria Chandra; Budianto, Budianto; Ningsih, Marsudi Lestari (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
Work performance issomething that is very important in a company or agency's efforts to achieve its goals.In order to improve employee performance, the role of leadership is a focus that attracts the attention of the field of organizational behavior. The quality of a leader is often considered the most important factor in determining the success or failure of an organization. The purpose of this study was to determine the effect of work stress, work motivation, organizational culture on work performance with leadership style as a moderation. The population used was employees at the Surabaya Police Polyclinic. The sampling technique used purposive sampling with a sample size of 38 people. The analysis techniqueusing parametric inferential statistical techniques, namely using the Partial Least Square (PLS) method as an alternative analysis tool using SMARTPLS 3.0. The test results show that work stress does not have a significant effect on the work performance of employees at the Surabaya Police Polyclinic. While work motivation and organizational culture have a significant effect on employee work performance. Leadership style is able to moderate the relationship between work stress and employee work performance and the relationship between organizational culture and employee work performance. Leadership style is not able to moderate the relationship between work motivation and employee work performance